機能素子を実装したカプセルレス小型発汗計の開発 - 芳賀, 洋一; 鶴岡, 典子; 鈴木, 啓二; 河野, 隆宏; 松永, 忠雄 (Transactions of Japanese Society for Medical and Biological Engineering, 2015)
The purpose of this study is to develop a wearable sized sweating rate meter. It is known that thermal sweating rate reflects deep body temperature and dehydration. Therefore, continuous sweat measurement with a small sudorometer is expected to contribute to the prevention of heat stroke. The distinctive features of developed device are wearable size, eliminated capsules and packaged functional elements such as an air pump and two humidity sensors on it. Sweating rate is determined by the conventional method that uses the humidity difference between ambient air and the air moistened by sweat. The fabricated device has functional elements and flow channel on flexible substrate. It was evaluated that the device could quantify the sweating rate within precision of 15 percent by measuring water in place of sweat. Also, increases in thermal sweating rate on forearm after passive heat stress were successfully measured with the developed device in all subjects.